Budget Institutions in Low-Income Countries : Lessons from G-20 - Gupta, Sanjeev (IMF Working Papers; Working Paper ;, 2014)
This paper presents twelve budget institutions that can support planning and delivery of credible fiscal strategies in the fiscal policy-making process. The resulting framework is applied to seven low-income countries and the status of their budget institutions compared to the G-20 advanced and emerging market economies. The paper then presents recommendations for designing and implementing appropriate fiscal strategy for low- income countries. Particular attention is paid to prioritization and sequencing of reform efforts.